ALTERNATIVE DISPUTE RESOLUTION (ADR) DALAM PENYELESAIAN SENGKETA KONSUMEN - Taufikkurrahman Taufikkurrahman (Institut Agama Islam Negeri Madura, 2015)
Consumers often consume goods and / or services resulting in damage, pollution and the loss on himself. So that the rights and obligations himself always disproportionate (balanced). So that consumer rights are not permanently harmed by businesses or otherwise, the Republic country of Indonesia established a law that became the basis for consumers, businesses, Non-governmental organization and the Government to take the legal actions as a result of violations committed by parties who are not responsible responsibility. Through UU No. 8 the year 1999 on Consumer Protection became the constitutional basis for businesses and consumers, especially in solving problems (disputes) that happened to himelf. Legal effort in problem solving (dispute) can use the lines outside the court (Non-Litigation) and through the courts (Litigation). The lines outside the court carried out by the Consumer Dispute Settlement Board (BPSK). BPSK in resolving disputes of consumer through mediation, arbitration or conciliation.